2013
DOI: 10.1007/s11669-013-0268-4
|View full text |Cite
|
Sign up to set email alerts
|

The Hafnium-Platinum Phase Diagram

Abstract: Phase relationships were determined in the Hf-Pt system at temperatures up to 1690°C using both metallographic and neutron Rietveld refinement techniques. An unusual displacive transformation is observed below 200°C in the rhombohedral compound Hf 3 Pt 4 , similar to that recently discovered in the compound Zr 3 Pt 4 . Crystallographic data are presented for the compounds HfPt 4 , HfPt 3 , Hf 2 Pt 3 , Hf 3 Pt 4 , HfPt, and Hf 2 Pt. A complete phase diagram is presented for the Hf-Pt binary system.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 17 publications
1
6
0
Order By: Relevance
“…[68]. Only 6 compounds of this prototype have been reported in transition metal binary systems: Ni 4 Ti 3 [69,70], Pd 4 Y 3 [71], Pd 4 Zr 3 [72], Pt 4 Zr 3 [73], Rh 4 Zr 3 [74], and most recently Hf 3 Pt 4 [75]. In these compounds, one component is a 3B or 4B element and the other is from the ninth or tenth column of the periodic table.…”
Section: Synergy Of Experimental and Calculation Data On A Rare Proto...mentioning
confidence: 99%
“…[68]. Only 6 compounds of this prototype have been reported in transition metal binary systems: Ni 4 Ti 3 [69,70], Pd 4 Y 3 [71], Pd 4 Zr 3 [72], Pt 4 Zr 3 [73], Rh 4 Zr 3 [74], and most recently Hf 3 Pt 4 [75]. In these compounds, one component is a 3B or 4B element and the other is from the ninth or tenth column of the periodic table.…”
Section: Synergy Of Experimental and Calculation Data On A Rare Proto...mentioning
confidence: 99%
“…Such simulations would be an invaluable extension to this work; however, the necessary tools to accomplish them on a similarly large scale are not yet mature. Note added in proof.-While this paper was being prepared for publication, a new experimental study identified the new compound Hf 3 Pt 4 , of prototype Pd 4 Pu 3 [63]. Our calculations show that this structure is metastable in the HfPt system, at 19 meV/atom above the convex hull, as well as in the HfPd and PdZr systems.…”
Section: Discussionmentioning
confidence: 82%
“…Here, we focused on the alloy systems consisting of only transition metals. In this review, the binary alloy systems were classified into six groups according to the type of bulk phase diagram as follows. Class 1 consists only of intermetallic phases; class 2 covers both intermetallic phases and solid‐solution phases (at least more than 10 at % of solid‐solution phases at 1000 °C); class 3 is mostly solid‐solution phases (more than 70 at % at 1000 °C); class 4 is all‐proportional solid solutions; class 5 is partly solid‐solution phases (less than 70 at % at 1000 °C), and class 6 covers completely immiscible systems.…”
Section: Pgm‐based Binary Alloy Systemsmentioning
confidence: 99%